Los Retos del Postconflicto desde un Enfoque Interdisciplinar - Luna Blanco, Tania María Camila (Corporación Universitaria Americana, 2022)
After the signing of the peace agreement between the government and the FARC guerrilla in 2016, Colombia must face new challenges posed by the post-conflict and peacebuilding. This initiative brought together professors and practitioners who have been working on the issues of conflict and peace from different perspectives. This book counted with the participation of academics and experienced professionals from different areas of knowledge such as law, political science, history and psychology for the approach from different perspectives of this transcendental topic for the country. One of the main challenges analyzed in this work is the need to rewrite the history of the conflict and include voices that have traditionally been absent. It proposes a change in the narratives of the Colombian armed conflict towards other revisionist and critical ones.